STRATEGI PROMOSI PERPUSTAKAAN DI MASA PANDEMI COVID-19 MENGGUNAKAN MEDIA SOSIAL - Puspita, Kadek Dian Dwinanda; Suhartika, I Putu; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 2 No 1 (2022), 2022)
The purpose of this study is to find out the strategy of library promotion during the Covid-19 pandemic using social media. The means of library promotion can be divided into two, namely means in printed form and means in electronic form. This type of research uses library research. The strategy is to determine the targets/targets of promotional activities, determine the promotional media to be used, plan concepts for promotional media, and disseminate promotional media on social media. Some social media that are often used such as: Instagram, Youtube, Facebook, Tiktok. Keywords: library promotion, promotion media, pandemic Covid-19